PEMANFAATAN VOIP PHONE SYSTEM SEBAGAI SARANA KOMUNIKASI JARINGAN LOKAL - Divi Handoko (STMIK KAPUTAMA, 2020)
Communication is a very important part in conveying information, especially voice information or voice, can be done in various ways, one of them using the telephone. Voice over Internet Protocol (VoIP) is a means of delivering information at a very low cost compared to analog phones and can be applied to existing office equipment, such as a computer, laptop and Android smartphone without the need to buy special devices. VoIP can be implemented using the internet (like WhatsApp) or on a local network (such as LAN or WLAN) which is very suitable to be implemented in companies or offices. VoIP can be implemented in companies in areas that are not affordable by the internet, VoIP is an alternative digital telephone technology in delivering information in the form of voice. The main objective of this research is to discuss the utilization and implementation of VoIP Phone voice communication systems using Local Area Network (LAN) or Wireless Local Area Network (WLAN) as a transmission media. VoIP phone systems require 2 device models, namely devices that serve as servers with the trixbox operating system and softphone on a client computer or laptop. Keywords: VoIP, softphone, Server, Client